High-Capacity Rock Anchors Provide Uplift Resistance For Concrete-Filled Steel Pipe Piles - A Case Study - James Weaver (Deep Foundations Institute, 2011)
During the past 16 years, the authors have successfully used high-capacity rock anchors installed inside open-ended pipe piles, driven to bedrock, to provide uplift and overturning resistance for various structures including piers, bridges, power plant components and commercial buildings. These systems were ultimately used on the projects due to a combination of high uplift forces or overturning moments on the structures and the relatively poor subsurface conditions present at the sites. Other, foundation systems such as rock-socketed drilled shafts and spin fin piles were considered but were found to be economically prohibitive or not technically feasible.